The Reformation and the Principles of the English Constitution in Disraeli's 'Young England' Novels. Issue 1 (1st April 2014) - Pereiro, James; Nockles, Peter; Westbrook, Vivienne
Abstract The article explores some aspects of the intellectual climate of the first half of the nineteenth century and the new ideas about race and national identity. These in turn help to explain contemporary changes in historical perspective, particularly in respect to the English Reformation. Disraeli's novels reflect the ideas of the time on the above topics and echo contemporary historians in their views on the Reformation, its causes, and the religious and social changes that it brought about.